1986
DOI: 10.1029/gm036p0001
|View full text |Cite
|
Sign up to set email alerts
|

Dilatancy of quartz gouge in pure shear

Abstract: Dilatancy in artificial fault gouge consisting of quartz sand is produced under pure shear loading conditions at shear stresses of about 1/2 the frictional shear failure strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In experiments [e.g., Teufel, 1981;Raleigh and Marone, 1986;Marone et al, 1990] the slip on a frictional surface is often accompanied by a plastic dilatancy inside the sheared zone. Although the existence and magnitude of this behavior in field processes is largely an unresolved issue, several analyses [Rudnicki and Chen, 1988;Segall and Rice, 1995] have shown that this dilatancy has a strong influence on the stability of the slip.…”
Section: Plastic Porosity Changesmentioning
confidence: 99%
“…In experiments [e.g., Teufel, 1981;Raleigh and Marone, 1986;Marone et al, 1990] the slip on a frictional surface is often accompanied by a plastic dilatancy inside the sheared zone. Although the existence and magnitude of this behavior in field processes is largely an unresolved issue, several analyses [Rudnicki and Chen, 1988;Segall and Rice, 1995] have shown that this dilatancy has a strong influence on the stability of the slip.…”
Section: Plastic Porosity Changesmentioning
confidence: 99%
“…Chinnery (1966a,b) also considered strikeslip movements in regions of pure shear and extension. Rayleigh & Marone (1986) suggested that, 'ideally', strike-slip faults are driven to failure by pure shear loading. Bombolakis (1976, fig.…”
Section: Introductionmentioning
confidence: 99%